2002
DOI: 10.5194/hess-6-363-2002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of throughfall water and chemistry and forest floor water content in a Douglas fir forest stand

Abstract: This study focuses on spatial variability of throughfall water and chemistry and forest floor water content within a Douglas fir (Pseudotsuga menziesii, Franco L.) forest plot. Spatial patterns of water and chemistry (NH 4 + , NO 3 -, SO 4 2-, Cl -, Mg 2+ , Ca 2+ , Na + and K + ) were compared and tested for stability over time. The spatial coefficient of variation (CV) was between 18 and 26% for amounts of throughfall water and ions, and 17% for forest floor water content. Concentrations and amounts of all io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 40 publications
(64 reference statements)
9
119
4
Order By: Relevance
“…This influence could result from reduced water input due to interception in the crowns, the buffering of mineral soil from large amounts of summer rainfall by organic layers (Leuschner 2002) or water extraction by tree roots (Schume et al 2003). In fact, a positive correlation between interception rates and stand density has been documented repeatedly (Raat et al 2002). For instance, Olszewski (1984) and Kozłowski (2003) found that the highest through fall in conifer and mixed stands occurred under crown edges and the lowest near the stem, with average differences amounting to over 100% of direct precipitation.…”
Section: Spatial Variation In Topsoil Propertiesmentioning
confidence: 99%
“…This influence could result from reduced water input due to interception in the crowns, the buffering of mineral soil from large amounts of summer rainfall by organic layers (Leuschner 2002) or water extraction by tree roots (Schume et al 2003). In fact, a positive correlation between interception rates and stand density has been documented repeatedly (Raat et al 2002). For instance, Olszewski (1984) and Kozłowski (2003) found that the highest through fall in conifer and mixed stands occurred under crown edges and the lowest near the stem, with average differences amounting to over 100% of direct precipitation.…”
Section: Spatial Variation In Topsoil Propertiesmentioning
confidence: 99%
“…Rainwater is thereby influenced by three main processes (Chiwa et al 2004): (1) the washing of deposits accumulated on the canopy between precipitation events, (2) the leaching of material from internal plant tissues and (3) the uptake by foliage of solutes. Tree species with different foliage properties exhibit different patterns of throughfall water and ion fluxes (Beier et al 1993;Hansen 1995;Raat et al 2002;Whelan et al 1998). Furthermore, as dry deposition is also a function of foliage properties (Lovett 1994), it may cause species-related differences (Hojjati et al 2009;Rothe et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Amounts of NH 4 + and/or NO 3 -added (Table 2) were calculated from the amounts of nitrogen added to the forest floor during a rain event (2.7 kg-N ha -1 ; Hansen et al 1994;Raat et al 2002), the molar ratio of NH 4 + :NO 3 -in throughfall (2.7:1; Draaijers et al 1998) and the total dry mass of the forest floor (3.2 kg m -2 ; Wessel and Tietema 1995). In this calculation we assumed that throughfall was distributed evenly over the top half of the forest floor.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…In an earlier study (Raat et al 2002), it was shown that during a rain event not only the forest floor is rewetted, but that simultaneously a large pulse of inorganic-N is added via throughfall. Recorded N pulses were as high as 2.7 kg-N ha -1 , equaling about 6.5% of the yearly atmospheric N deposition.…”
Section: Introductionmentioning
confidence: 99%